Respons Biologi Wereng Batang Coklat terhadap Biokimia Tanaman Padi - Rahmini, Rahmini; Hidayat, Purnama; Ratna, Endang Sri; Winasa, I Wayan; Manuwoto, Syafrida (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2012)
In developing rice varieties resistant to brown planthopper (BPH), information on responses of the BPH to the rice plants were needed. The aim of the research was to study the biological responses of BPH on biochemical factors of some rice varieties. The study was conducted on June 2010 to April 2012 in Muara Research Station, of the Indonesian Center for Rice Research (ICRR) and at Laboratory of Physiology and Toxicology, Plant Protection Department, Bogor Agriculture University. The biological responses of the BPH to rice varieties were studied in terms of adult settling preference, feeding activity using the honeydew test, and life table analysis. The biochemical factors of the rice varieties, namely sucrose and oxalic acid contents were analyzed. Rice varieties TN1 (no resistance gene), IR26 (Bph1), IR42 (bph2), IR64 (Bph1+), IR74 (Bph3), PTB33 (bph2+Bph3), and Inpari13 (unknown resistance gene) were used in this study. The BPH showed similar non-preference reactions to the resistant varieties and Inpari13 for settling. Feeding activity of the adult female BPH was the highest on the susceptible variety TN1 and the lowest on the resistant variety PTB33. The highest mortality of BPH occurred at larval stages, especially in the first and second instars. The intrinsic rate of increase (rm) and net reproductive rate (Ro) of the BPH were higher on the susceptible variety TN1, but the doubling time (DT) was shorter than those on the resistant varieties. The resistant variety PTB33 contained high oxalic acid and low sucrose. On the contrary, the susceptible variety TN1 contained low oxalic acid and high sucrose. These biochemical factors contributed in rice plant resistance to BPH.